Analysis of Implementation of Postpartum Exercise on Breast Milk Production and Uterine Involution in Postpartum Mothers in Makassar - Hasiba Hasiba; Satiani Dalle; Sudin (Jurnal Life Birth, 2023)
Postpartum exercise has a positive effect on the health status of the mother, including helping to normalize joints that become loose due to pregnancy and childbirth and preventing further weakness and stretching. Postpartum exercise exercises can be done within 24 hours after giving birth and then regularly every day (Diana, 2014). However, the reality obtained in the field is that postpartum exercise is rarely carried out because mothers are afraid to make many movements, still have pain in the perineal wound area and are afraid of the stitches coming off. General Objectives To determine the effect of implementing postpartum gymnastics on the smoothness of breastfeeding and uterine involution, Specific Objectives To find out the effect of implementing postpartum gymnastics on the production and smoothness of breast milk, and to know the effect of implementing postpartum gymnastics on uterine involution. this type of Quasi Experiment research uses the theNon-Equivalentt Control Group design, namely a study that compares the case group with the control group. The population of this study was 59 people and the sample in this study was part of normal postpartum mothers from day 2 to day 4 and were willing to be respondents. Based on the distribution of postpartum exercise movements on breast milk production, it shows that there is no influence between postpartum exercise movements and the smooth production of breast milk and based on the distribution of postpartum exercise movements on uterine involution. shows that postpartum exercise has a significant effect on uterine involution variables